The Role of Company Standards in Supply Chains – The Case of the German Automotive Industry - Anne-Marie Großmann; Paul von Gruben (Innovative Methods in Logistics and Supply Chain Management: Current Issues and Emerging Practices. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Company standards cover aspects such as quality assurance, testing procedures and terms of delivery. They are used not only internally but also imposed on suppliers. In this function, company standards have a potential to facilitate knowledge diffusion along the supply chain as well as assuring supplier's quality and have an impact on the bargaining power equilibrium between the buyer and its supplier. Especially in the automotive industry these aspects play an important role. This article uses a mixed methods approach to explore the employment of company standards in the supply chain of the German automotive industry with a special focus on the company's position within this supply chain. We analyze quantitative data from the German standardization panel to map the usage of company standards on different stages of the supply chain. An extensive qualitative analysis reveals how company standards play a role in the automotive supply chain. By examining the network that company standards span between manufacturers, suppliers and raw material producers we are able to highlight the various ways of diffusion of codified knowledge along the supply chain. This analysis reveals that especially large and powerful downstream players are able to burden their company standards on their suppliers but also upstream producers can provide their standards to their customers. Suppliers use different tactics to deal with heterogeneous external company standards they receive from their buyers. The results show that company standards can be a tool to manage the delivered quality of suppliers in the automotive industry but the different company standards of multiple buyers can lead to increased efforts on part of the supplier.
10419/209188; https://econpapers.repec.org/RePEc:zbw:hiclpr:19
Keywords: 650; company standards; standardization management; supplier management; supply chain management